Effect of CCL5 expression in the recruitment of immune cells in triple negative breast cancer - Bravo, Leny (2018)
Triple negative breast cancer (TNBC) is the most aggressive form of breast cancer with limited options of targeted therapy. Recent findings suggest that the clinical course of TNBC may be modified by the presence of tumor-infiltrating lymphocytes (TILs) and chemokine’s expression, such as CCL5. Diverse studies have shown that CCL5 suppresses anti-tumor immunity and it has been related to poor outcome in different types of cancer while in other studies, this gene has been related with a better outcome. We sought to determine the association of CCL5 with the recruitment of TILs and other immune cells. With this aim we evaluated a retrospective cohort of 72 TNBC patients as well as publicly available datasets. TILs were correlated with residual tumor size after neoadjuvant chemotherapy (NAC) and CCL5 expression. In univariate analysis, TILs and CCL5 were both associated to the distant recurrence free survival; however, in a multivariate analysis, TILs was the only significant marker (HR = 0.336; 95%IC: 0.150–0.753; P = 0.008). CIBERSORT analysis suggested that a high CCL5 expression was associated with recruitment of CD8 T cells, CD4 activated T cells, NK activated cells and macrophages M1. The CD8A gene (encoding for CD8) was associated with an improved outcome in several public breast cancer datasets.